Creating theory that works - Mohd Ridzuan, Darun
Every time a corporate scandal is on a breaking news, professors are normally among the first being interviewed to share their views of "What went wrong?". Educators are extoling how much their academic curricula promoting the importance of human governance and business ethics. Professionals are pressured to figure out a quick solution or standards to prevent scandals for good. Regulators and policymakers are forced to rewrite policies to tighten control and enforcement. New measures are being introduced to monitor business conducts and process. Textbooks admiring troubled companies are being taken off the shelves, and educators are asked to hurriedly refurbish academic curricula to produce graduates with dedication, transparency, and honesty